Rural-urban differentials in women empowerment and experience of under-five mortality among mothers in Nigeria: a Multiple Indicator Survey analysis - Praise Ooreoluwa Onakalu; Funmilola Folasade Oyinlola; Omolayo Bukola Oluwatope; Ifedapo Agbeja; Immanuel O Shittu; Gbemisola Bolanle Ogbeye; Kwala Adline Okorafor (BMC Public Health)
Abstract Background Under-five mortality remains a significant concern in low and middle-income countries, with sub-Saharan Africa accounting for 57% of all under-five deaths. Nigeria has one of the highest under-five mortality rates, with approximately 107 deaths per 1000 live births due to preventable causes. Empowering women is a crucial strategy for improving child survival, but there are notable variations in women’s empowerment across Nigeria, which have profound implications for maternal and child health. This study investigated the differences in women’s empowerment between rural and urban areas and its impact on under-five mortality in Nigeria. Methods This cross-sectional study utilized secondary data from the 2021 Nigeria Multiple Indicator Cluster Survey (MICS), with a weighted sample size of 38,586 women of reproductive age. Respondents’ characteristics were described by summary statistics, relationships between variables were examined using chi-squares and logistic regression analysis while controlling for potential confounding factors. Analysis was performed using Stata version 17. Results The study found that urban residents reported lower under-five mortality rates across most socio-demographic factors. Empowered women, regardless of their residence, were less likely to experience under-five mortality compared to non-empowered women. However, rural women exhibited lower levels of empowerment and social independence compared to their urban counterparts and were more likely to justify domestic violence. Women’s empowerment has a significant influence on the experience of under-five mortality, revealing that women who reported being empowered are 27% less likely (OR = 0.731, p = 0.001) to experience under-five mortality as compared to those not empowered. Conclusions The study highlighted significant rural-urban disparities in women’s empowerment and under-five mortality rates in Nigeria. To improve under-five mortality rates, interventions focusing on mothers’ social independence and empowerment (socially, economically, and educationally) with a particular emphasis on promoting women’s empowerment in rural areas. Targeted interventions should also address poor societal attitudes towards violence.